TEMPORAL AND LOCATIVE PREPOSITIONS VERSUS ADVERBS: LEXICAL AND GRAMMATICAL OVERLAPPING (CORPUS-BASED STUDY) - Yurii Kovbasko (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2016)
The paper focuses on an essential problem of a "part-of-speech" theory, including temporal and locative prepositions and adverbs overlapping in lexical and grammatical perspective. The study is pursued on a corpus-based approach towards prepositions and adverbs overlapping in present-day English (PDE), giving consideration to the complements applied. The latter are divided into two wide groups, namely Noun Phrase and Alternative Complements. To organise the results the comparative-parametric method of linguistic research developed by Sternina was introduced. A comparison has been made between traditional interpretation of complement use and practical corpus-based results in PDE. It has been ascertained that among 94 lexical units treated as one-word prepositions 49 units show overlapping of prepositions and adverbs; however, 39 units bear locative and temporal semes. The results of the PDE corpus-based research show that conventional interpretation of prepositions as lexical units governing Noun Phrase Complements and Adverbs as units correlating with Alternative Complements is deceptive, as it is based on a synchronic syntactic approach, neglecting diachronic syntax and semantics. The hypothesis proposed describes a necessity to reconsider modern PoS division theory, taking into account diachronic approach and analysis of lexical units at the stages of their genesis in Old English and Middle English periods.